Papua at the Crossroads: A Plea for Systematic Conservation Planning in One of the Largest Remaining Areas of Tropical Rainforest - Parsch, Christoph; Wagner, Benjamin; Pangau-Adam, Margaretha; Nitschke, Craig; Kreft, Holger; Schrader, Julian (Frontiers in Forests and Global Change, 2022)
Land-use change has progressed rapidly throughout the Indonesian archipelago and is now intruding into western New Guinea (Tanah Papua), one of the world’s last wilderness areas with extensive tracts of pristine and highly diverse tropical rainforests. Tanah Papua has reached a crossroads between accelerating environmental degradation and sustainable development policies entailing landscape-scale conservation targets, pledged in the Manokwari Declaration. We assessed the representation of ecoregions and elevational zones within Tanah Papua’s protected area network to identify its shortcomings at broad spatial scales. Lowland ecoregions are less protected than mountainous regions, with half of the western and southern lowlands designated for land-use concessions. Under the direct threat from land-use change, the political motivation in Tanah Papua toward conservation- and culture-centered land management provides a window of opportunity for scientifically guided, proactive conservation planning that integrates sustainable development for the benefit of Indigenous communities.